Path to the “soft hegemony” in the Middle East of the Obama Administration (International relations and international law Journal, 2016)
The direction of the Middle East, which constantly stays of current importance for many decade, takes an important place in the U.S. foreign policy. During the election campaign of Barack Obama, the candidate of the Democratic Party, he actively gave promises to voters in those formulations and concepts that the country’s society wished to hear in 2008, such as the withdrawal of U.S. troops from Afghanistan and reduction of military actions. In domestic policy these promises were related to the social problems required resolution through the radical reforms in the American health care system. Barack Obama’s political promises, greatly enhanced the reputation and image after his election as the country’s president, led to increasing in the number of Obama’s political supporters abroad. The Middle East in changing geopolitical conditions context remains a “hot spot” of world politics and respectively of the United States. In this article we’ll try to analyze the essence of this country’s foreign policy on the example of one direction and answer the following questions: does it differ from the politics pursued by the previous presidents George HW Bush and George W. Bush and what changes were made to the foreign policy of the United States.
Keywords: U.S. Foreign Policy; Conflict; Middle East; President